Development and Validation of Pesticide Residues Determination Method in Fruits and Vegetables through Liquid and Gas Chromatography Tandem Mass Spectrometry (LC-MS/MS and GC-MS/MS) Employing Modified QuEChERS Method and a Centrifugal Vacuum Concentrator - Styliani E. Romniou; Konstantina Nana; Marilena Dasenaki; Efstratios Komaitis; Charalampos Proestos (Agriculture, 2022)
Pesticides are used for controlling organisms, weeds and animals, causing damage to plants. Although the use of pesticides is a prerequisite for producing safe food, their accumulation makes their rapid determination necessary to avoid negative impacts on human health. The aim of this study was to develop reliable and robust analytical methods for the determination of pesticide residues in fruits and vegetables, validated according to SANTE/12682/2019 guidance. Five different categories of fruits and vegetables were selected (apple, orange, onion, lettuce, tomato). The sample preparation was based on QuEChERS methodology, slightly modified in the clean-up step, and appropriate d-SPE reagents were selected for each commodity. A Multi-Tube Vortexer was used for better agitation. In the final step, the extract was split in two: one part was acidified and injected in LC-MS/MS and the other part was evaporated in a centrifugal vacuum concentrator, and reconstituted and injected in GC-MS/MS. With the centrifugal vacuum concentrator used instead of nitrogen stream, more pesticides were determined, while sensitivity and repeatability increased. Validation results satisfied the SANTE/12682/2019 guidelines for approximately 220 analytes for each commodity. LOQ was set at 0.010 mg/kg for all analytes. Successful external quality assessment (proficiency testing) proved that the methods are fit for purpose.